AFRICANIZING REBEL INSURGENCY IN A POST-COLONIAL STATE AND RAMIFICATIONS FOR AFRICAN REGIONAL INTEGRATION: INSIGHT(S) FROM THE DEMOCRATIC REPUBLIC OF CONGO (DRC) - Mlambo, Daniel (Universitas Nasional, 2021)
This article aims to ponder the effects of political instability and, rebel insurgency, in particular, have on Africa’s regional integration frameworks by drawing insights from the Democratic Republic of Congo (DRC). The upsurge of militias has been a norm in some African countries such as the Central African Republic, Somalia and Sudan. This article utilized a qualitative method. When one adopts this type of method, s/he anticipates gathering a robust viewpoint pertaining to human behaviour and the rationale behind it. Data retrieved was drawn from secondary sources such as books, chapters in books, journal articles, credible online sources and policy briefs that monitor African conflict (especially the DRC). Similarly, the political instability that continues to take centre stage in the DRC because of many and diverse rebel groups fighting for the country’s prestigious resources has produced a web of both internal and external instability, further crippling the country’s economy, neighbouring countries and Africa’s regional integration blueprints.